Simplified automatic VAR/Power factor compensator using fuzzy logic based on internet of things. (April 2019) - Luqman, A N; Lestari, N S; Setiawan, I
Abstract: In AC Power Systems, the compensation of reactive power is very important to support both of load and grid voltage. Generally, the objective of every reactive power compensators is to improve power factor that is the ratio of real power with apparent power to supplied the load. The main aim of this paper is twofold. Firstly, to design and realize a power factor corrector so the system's power factor is kept high, secondly to monitor energy consumed by the load using IoT technology. The uniqueness of this work is that to improve system power factor, we used capacitor bank which are composed from several capacitor with different values. The software is embedded in a low-cost microcontroller then will activate a unique combination of the capacitor by using successive approximation algorithm such that the power factor compensator more reliable; in this case, the damage of one or several capacitors in bank will not degrade the performance of the power factor compensator too much.